Features of Electro-Induced Periodical Structures in LiTaO3 Single Crystal and Their Interaction with Surface Acoustic Wave - Siarhei D. Barsukou; Jun Kondoh; Sergei A. Khakhomov (Advances in Materials Science and Engineering)
In this research, the features of electro-induced periodical structures in the volume of LiTaO3 thin plate were theoretically and experimentally investigated. For the theoretical and experimental investigations, the calculations based on the finite element method and measuring of the surface acoustic wave (SAW) interaction were implemented simultaneously. The observed difference of the electro-induced structures provides a new opportunity to control of the acoustic wave propagation in a ferroelectric substrate. The volume-existed periodical structures were induced as different electric potentials were applied to the surface arranged electrodes. The features of the induced structure were theoretically investigated based on a developed theoretical unit cell model for different induced structure configurations. The properties of the acoustic wave interaction with the periodical structure were studied on the basis of a theoretical full 3D model of an SAW device. A novel controllable SAW device was fabricated and studied experimentally. The experimental results show significant differences in magnitude and phase of both reflected and transmitted signals depending on the induced structure configuration.